Diversion Formulation in Handling of General Criminal Actions Based on Justice Value - Riya Novita, I Gusti Ayu Ketut Rachmi Handayani, Sri Endah Wahyuningsih (International Journal of Advanced Science and Technology, 2020)
The law enforcement system in Indonesia makes law enforcement officials namely the Police, Prosecutors and Judges bound to a system that requires that the perpetrators of a criminal offense must be convicted and undergo punishment in prison. The purpose of this research is to find out and analyze the effectiveness of handling general criminal offenses in the criminal justice system in Indonesia and then applying the diversion model in handling general criminal offenses. Research methods with constructivism paradigm. Juridical sociological approach. Research data sources consist of primary data sources and secondary data sources, with qualitative descriptive analysis. That Indonesia requires the completion of criminal cases that not only emphasize the imposition of crimes against perpetrators, but the return of conditions in their original form or the restoration of equilibrium which is disturbed in society, due to criminal acts that occur. Some general criminal acts actually do not need to go through a trial process because in practice there is often a peace between the perpetrator and the victim, but because positive law in Indonesia is not regulated in formal or material law, it does not guarantee that the agreement can be implemented or the case is terminated the process, so it is hoped that through the diversion process, it will reduce the cases that go to court and also create a sense of justice for victims, because the essence of diversion is to divert a case from the judicial process, so that it is hoped that through the diversion process justice can be achieved both for the perpetrators and victims and also reduce case headings, reduce over prison capacity to save the state budget in handling criminal acts.